2021
DOI: 10.3389/fvets.2021.619889
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Interventions to Improve Neonatal Survival on British Beef and Sheep Farms: A Qualitative Study

Abstract: Neonatal lamb and calf deaths are a major issue in UK agriculture. Consistent mortality rates over several decades, despite scientific advances, indicate that socioeconomic factors must also be understood and addressed for effective veterinary service delivery to improve lamb and calf survival. This qualitative study utilised semi-structured interviews with vets and farmers to explore the on-farm mechanisms and social context, with a particular focus on the role of the vet, to manage and reduce neonatal losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…That said, farmers demonstrate significant autonomous motivation to improve survival, with a strong desire to make improvements because ‘it's the right thing to do’, rather than due to external factors such as judgement by other farmers or the advice of their vet (AHDB and others 2020). External factors, such as the weather or lack of finance to invest in buildings, are often given by farmers as barriers to change; however, detailed interviews have shown that there is also an emotional barrier and stigma to considering losses, with clear impacts on mental health (Adam and others 2021).…”
Section: Engaging Farm Managers In Lamb Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…That said, farmers demonstrate significant autonomous motivation to improve survival, with a strong desire to make improvements because ‘it's the right thing to do’, rather than due to external factors such as judgement by other farmers or the advice of their vet (AHDB and others 2020). External factors, such as the weather or lack of finance to invest in buildings, are often given by farmers as barriers to change; however, detailed interviews have shown that there is also an emotional barrier and stigma to considering losses, with clear impacts on mental health (Adam and others 2021).…”
Section: Engaging Farm Managers In Lamb Survivalmentioning
confidence: 99%
“…Losses that are seen to be unavoidable or accidental are perceived as more acceptable, and this supports the common observation that many farms have a level of tolerated losses, below which intervention is not warranted. The threshold beyond which tolerated losses are no longer tolerated, hence triggering veterinary involvement, appears to vary hugely between farms, with experience, circumstances and the relationship with the vet playing an important role (Adam and others 2021).…”
Section: Engaging Farm Managers In Lamb Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of peers or peer pressure on farmer behaviour has previously been demonstrated (Farrell et al, 2021) and is revealed in this study, as farmers reported seeking advice on diagnosis and treatment from peers rather than professionals. Specific testimonial from peer farmers about a disease and its treatment through educational activities has been shown to assist in uptake of recommended guidelines (Spence, 1951;Adam et al, 2021), and this should be encouraged in relation to sheep scab control programmes.…”
Section: The Role Of Trusted Advisorsmentioning
confidence: 99%